PENGARUH KUALITAS PELAYANAN BPJS KESEHATAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI UPTD PUSKESMAS BANDAR KOTA PAGAR ALAM - Yesita Astarina; Deki Fujiansyah; Ruaman Yudianto (Jurnal Ekonomia, 2021)
The aims of this study were 1) to determine the effect of BPJS Health service quality on outpatient satisfaction at UPTD Bandar Kota Pagar Alam Health Center, 2) to determine the relationship between BPJS Health service quality and outpatient satisfaction at UPTD Puskesmas Bandar Kota Pagar Alam. The research method used is associative research type. Primary data were obtained from questionnaires distributed to 96 respondents who were outpatients at the UPTD Puskemas Bandar Kota Pagar Alam. Secondary data was obtained through literature study (relevant books and literature) and agency internal data. The indicators used were obtained from this study, namely the dimensions of BPJS Service Quality (X) and the dimensions of Patient Satisfaction (Y). Based on the results of the analysis of research that has been done, that the correlation calculation in this study, the effect of service quality (X) on patient satisfaction (Y) the correlation value of 0.608 means that there is a correlation value in a strong level and a positive sign on the correlation coefficient indicates a unidirectional relationship between quality service (X) with patient satisfaction variable (Y) at UPTD Puskesmas Bandar Kota Pagar Alam. There is an influence of service quality on patient satisfaction of UPTD Puskesmas Bandar Kota Pagar Alam. Based on this statement, it means that Ha can be accepted.